Prevalence and factors associated with optic disc grey crescent in the Primary Open-Angle African Ancestry Glaucoma Genetics (POAAGG) Study. Issue 1 (14th February 2023) - Daniel, Ebenezer; Gao, Jinpeng; Maguire, Maureen G; Ying, Gui-shuang; Gudiseva, Harini V; Salowe, Rebecca; Addis, Victoria; Sankar, Prithvi S; Lee, Roy; Smith, Eli J; O'Brien, Joan
Abstract : Aim: To investigate the prevalence and factors associated with optic disc grey crescent (GC) in African Americans with glaucoma. Methods: Stereo optic disc image features from subjects with glaucoma in the Primary Open-Angle African Ancestry Glaucoma Genetics Study were evaluated independently by non-physician graders and discrepancies adjudicated by an ophthalmologist. Risk factors for GC were evaluated by logistic regression models with intereye correlation accounted for by generalised estimating equations. Adjusted ORs (aORs) were generated. Results: GC was present in 227 (15%) of 1491 glaucoma cases, with 57 (3.82%) bilateral and 170 (11.4%) unilateral. In multivariable analysis, factors associated with GC were younger age (aOR 1.27, 95% CI 1.11 to 1.43 for every decade younger in age, p=0.001), diabetes (aOR 1.46, 95% CI 1.09 to 1.96, p=0.01), optic disc tilt (aOR 1.84, 95% CI 1.36 to 2.48, p<0.0001), a sloping retinal region adjacent to the outer disc margin (aOR 2.37, 95% CI 1.74 to 3.32, p<0.0001) and beta peripapillary atrophy (aOR 2.32, 95% CI 1.60 to 3.37, p<0.0001). Subjects with GC had a lower mean (SD) value of the ancestral component q0 than those without GC (0.22 (0.15) vs 0.27 (0.20), p=0.001), consistent with higher degrees of African ancestry. Conclusions: More than 1 in 10 glaucoma cases with African ancestry have GC, occurring more frequently in younger subjects, higher degrees of African ancestry and diabetes. GC was associated with several ocular features, including optic disc tilt and beta peripapillary atrophy. These associations should be considered when evaluating black patients with primary open-angle glaucoma.